Mettl14 is required for mouse postimplantation development by facilitating epiblast maturation - Meng, Tie-Gang; Lu, Xukun; Guo, Lei; Hou, Guan-Mei; Ma, Xue-Shan; Li, Qian-Nan; Huang, Lin; Fan, Li-Hua; Zhao, Zheng-Hui; Ou, Xiang-Hong; OuYang, Ying-Chun; Schatten, Heide; et al. (The FASEB journal, 2019)
N6-methyladenosine (m A) is the most prevalent and reversible internal modification of mammalian messenger and noncoding RNAs mediated by specific m A writer, reader, and eraser proteins. As an m A writer, the methyltransferase-like 3-methyltransferase-like 14 (METTL14)-Wilms tumor 1-associated protein complex dynamically regulates m A modification and plays important roles in diverse biologic processes. However, our knowledge about the complete functions of this RNA methyltransferase complex, the contributions of each component to the methylation, and their effects on different biologic pathways are still limited. By using both in vivo and in vitro models, we here report that METTL14 is indispensable for postimplantation embryonic development by facilitating the conversion from naive to primed state of the epiblast. Depletion of Mettl14 leads to conspicuous embryonic growth retardation from embryonic d 6.5, mainly as a result of resistance to differentiation, which further leads to embryonic lethality early in gestation. Our data highlight the critical function of METTL14 as an m A modification regulator in orchestrating early mouse embryogenesis.-Meng, T.-G., Lu, X., Guo, L., Hou, G.-M., Ma, X.-S., Li, Q.-N., Huang, L., Fan, L.-H., Zhao, Z.-H., Ou, X.-H., OuYang, Y.-C., Schatten, H., Li, L., Wang, Z.-B., Sun, Q.-Y. Mettl14 is required for mouse postimplantation development by facilitating epiblast maturation.